2016
DOI: 10.1001/jamaoto.2015.3810
|View full text |Cite
|
Sign up to set email alerts
|

Depression-Specific Outcomes After Treatment of Chronic Rhinosinusitis

Abstract: IMPORTANCE Depression is frequently undiagnosed in patients with chronic rhinosinusitis (CRS) and affects quality of life, productivity, and health care use. OBJECTIVE To examine depression-specific outcomes after medical or surgical treatment of CRS. DESIGN, SETTING, AND PARTICIPANTS A multi-institutional, prospective study of patients with refractory CRS treated at tertiary academic rhinology centers was performed from March 1, 2011, to November 1, 2015. Data analysis was performed from October 1, 2015, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 22 publications
3
62
0
Order By: Relevance
“…19 With regard to depression, there were no studies that used strict Diagnostic and Statistical Manual of Mental Disorders, 4th Edition criteria. 20 Nine studies used a validated questionnaire to screen for depression, 9,11,[13][14][15][16][17][18][19] and four studies relied on a previous physician diagnosis. 7,8,10,12 There were four studies that used physician-diagnosed depression (n ϭ 631 patients).…”
Section: Systematic Review Of a Positive Depression Screen Results Inmentioning
confidence: 99%
See 4 more Smart Citations
“…19 With regard to depression, there were no studies that used strict Diagnostic and Statistical Manual of Mental Disorders, 4th Edition criteria. 20 Nine studies used a validated questionnaire to screen for depression, 9,11,[13][14][15][16][17][18][19] and four studies relied on a previous physician diagnosis. 7,8,10,12 There were four studies that used physician-diagnosed depression (n ϭ 631 patients).…”
Section: Systematic Review Of a Positive Depression Screen Results Inmentioning
confidence: 99%
“…The only study to use PHQ2 was also the largest (n ϭ 685 patients) and reported a prevalence of 24.4% 17 (Table 1). Two studies used PHQ9, and both reported a prevalence of 25% (Table 1).…”
Section: Systematic Review Of a Positive Depression Screen Results Inmentioning
confidence: 99%
See 3 more Smart Citations